Karakteristik kemampuan pemahaman konsep siswa kelas VIII di MTs az-zahra parongpong berdasarkan gender - Damayanti, Yuyun; Anita, Ika Wahyu (IKIP Siliwangi, 2023)
The purpose of this study was to identify and analyze the characteristics of students' ability to understand mathematical concepts in grade VIII. Descriptive qualitative research was used in this study. With regard to the subject of eighth grade students, MTs. Az-Zahra Parongpong has a total of 33 students, with 18 female students and 15 male students. The technique in collecting data is with 3 questions in the form of descriptions, each of which represents an indicator of mathematical concept understanding ability. The data processing technique is to analyze the ability to understand the mathematical concepts of the system of linear equations of two variables in terms of gender on each indicator. Based on the results of the analysis, the average score of male students is 40.3% and female students is 53.5% on the material of the system of linear equations of two variables. So with that difference, it can be said that the mathematical communication skills of female students are higher than male students.